CD34+ cell mobilization, blood graft composition, and posttransplant recovery in myeloma patients compared to non‐Hodgkinʼs lymphoma patients: results of the prospective multicenter GOA study - Turunen A (WILEY, 2022)
BACKGROUND
Autologous stem cell transplantation is an established treatment option for patients with multiple myeloma (MM) or non‐Hodgkinʼs lymphoma (NHL).
STUDY DESIGN AND METHODS
In this prospective multicenter study, 147 patients with MM were compared with 136 patients with NHL regarding the mobilization and apheresis of blood CD34+ cells, cellular composition of infused blood grafts, posttransplant recovery, and outcome.
RESULTS
Multiple myeloma patients mobilized CD34+ cells more effectively (6.3 × 106/kg vs. 3.9 × 106/kg, p = 0.001). The proportion of poor mobilizers (peak blood CD34+ cell count <20 × 106/L) was higher in NHL patients (15% vs. 3%, p < 0.001). Plerixafor was added to rescue the mobilization failure in 17 MM patients (12%) and in 35 NHL patients (26%; p = 0.002). The infused grafts contained more natural killer (NK) and CD19+ cells in MM patients. Blood platelet and NK‐cell counts were higher in MM patients posttransplant. Early treatment‐related mortality was low in both groups, but NHL patients had a higher late (>100 days) nonrelapse mortality (NRM; 6% vs. 0%, p = 0.003).
CONCLUSIONS
Non‐Hodgkinʼs lymphoma and MM patients differ in terms of mobilization of CD34+ cells, graft cellular composition, and posttransplant recovery. Thus, the optimal graft characteristics may also be different.